Agrobacterium From biology to biotechnology - Tzfira, Tzvi; Ed. Citovsky, Vitaly; Ed (springer, 2008)
Describes Agrobacterium's biology, interactions with host species, and uses for genetic engineering. Agrobacterium is the tool of choice for plant genetic engineering with an ever expanding host range that includes many commercially important crops, flowers, and tree species.